The Oral Glucose Tolerance Test: An Old but Irreplaceable Test to Evaluate Glucose Metabolism and Cardiovascular Risk - Fra, Gian Paolo; Bartoli, Ettore; Schianca, Gian Piero Carnevale (IntechOpen, 2011)
None